Method for evaluating conductivity of carbon source
By sintering the carbon layer in the carbon source with low conductivity and rough surface, the carbon source conductivity is evaluated, and the problems of cumbersome evaluation process, materials consumption and high cost in the prior art are solved, and a fast, accurate and low-cost evaluation effect is achieved.
Patent Information
- Application Number
- CN202411110009.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has complicated processes when evaluating the conductivity of carbon sources, which consumes materials to be coated, which is costly and takes a long time, resulting in waste of energy consumption.
The base ball with low conductivity and rough surface is used as the core, and placed in a solution of the carbon source and/or carbon source. After removal, sintering is made to form a carbon layer. The resistance value of the carbon layer is tested to evaluate the conductivity of the carbon source.
It realizes rapid and low-cost evaluation of carbon source conductivity, reduces the waste of materials to be coated, short time and high accuracy.
Smart Images

Figure CN119827836A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a method for evaluating the conductivity of a carbon source. Background Art
[0002] In secondary batteries, positive electrode active materials and negative electrode active materials are generally required to have good conductivity. However, many positive electrode active materials and negative electrode active materials do not meet the conductivity requirements when used directly. Therefore, they need to be modified by carbon coating during the preparation process.
[0003] Carbon coating modification usually requires a carbon source. However, there are many types of carbon sources. When screening, the positive electrode active material or the negative electrode active material needs to be carbon coated and modified first, and then evaluated. The above process is complicated and will also consume the positive electrode active material or the negative electrode active material, which is costly.
[0004] Therefore, it is crucial to develop a method to evaluate the conductivity of carbon sources that can overcome the above-mentioned shortcomings. Summary of the invention
[0005] In view of the above problems, the present application provides a method for evaluating the conductivity of a carbon source. The evaluation method can preliminarily determine whether a certain carbon source is suitable for carbon-coating a material to be coated, and can also preliminarily determine whether the carbon source has good film-forming properties on the surface of the material to be coated; it can also quickly and inexpensively screen out carbon sources suitable for carbon-coating the material to be coated from a large number of carbon sources; the evaluation method is time-saving, highly accurate, reduces waste of materials to be coated, and is low-cost.
[0006] The present application provides a method for evaluating the conductivity of a carbon source, the method comprising the following steps: setting the conductivity to ≤10 4 The substrate ball with S / m and rough surface is placed in a carbon source and / or a solution of a carbon source, the substrate ball is taken out and sintered to form a carbon layer, the resistance value of the carbon layer is tested, and the conductivity of the carbon source is evaluated.
[0007] In the technical solution of the implementation mode of the present application, the evaluation method uses a substrate ball with low conductivity and rough surface as the core, places it in a carbon source and / or a solution of a carbon source, takes it out and sinters it to form a carbon layer coated on the surface of the substrate ball, and tests the resistance value. In the evaluation method, there is no need to prepare the material to be coated (i.e., the positive electrode active material or the negative electrode active material) and the carbon source into a composite material through a complex process for judgment. It is only necessary to simply and quickly evaluate whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the material to be coated at the carbon source level, and make an advance guidance. The evaluation method is convenient and fast, can save energy and reduce consumption, and does not waste the material to be coated. When rapid screening is required from multiple carbon sources, the advantages of energy saving and efficiency improvement are obvious.
[0008] In some embodiments, the conductivity of the substrate ball is 10 -8 ~10 4 S / m.
[0009] In the technical solution of the implementation mode of the present application, the conductivity of the base ball is within the range, which belongs to a semiconductor material and can effectively evaluate whether the carbon coating layer of the carbon source after carbonization can effectively improve the electronic conductivity of the semiconductor material to be coated.
[0010] In some embodiments, the material of the base ball includes silicon carbide.
[0011] In some embodiments of the present application, the material of the base ball is within the above-mentioned range, has a wide source of raw materials, is low in cost, has high hardness, and is resistant to high temperatures, and can meet the requirements of sintering by coating with a variety of carbon sources. It can also be low-cost and efficient to evaluate whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the semiconductor material to be coated.
[0012] In some embodiments, the conductivity of the substrate sphere is less than 10 -14 S / m.
[0013] In the technical solution of the implementation mode of the present application, the conductivity of the base ball is within the range, which belongs to an insulating material, and can effectively evaluate whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the insulating material to be coated.
[0014] In some embodiments, the material of the base ball includes any one of aluminum oxide, zirconium dioxide, or silicon dioxide, or a combination of at least two of them.
[0015] In the technical solution of the implementation mode of the present application, the material of the base ball is within the above-mentioned range, the raw material source is wide, the cost is low, and the insulation is good. It can evaluate at low cost and efficiently whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the insulating material to be coated.
[0016] In some embodiments, the surface roughness of the base ball is 0.4-6.0 μm.
[0017] In the technical solution of the implementation mode of the present application, the surface roughness of the substrate ball is within the above range, the carbon source or the solution of the carbon source has good wettability on its surface, the substrate ball can have a good interaction force with the carbon source, which is conducive to forming a carbon layer that meets the requirements.
[0018] In some embodiments, the diameter of the substrate sphere is 0.8 to 1.5 cm.
[0019] In the technical solution of the embodiment of the present application, the diameter of the base ball is within the above range, and the tension of the carbon source on its surface is moderate, which is conducive to the experiment and convenient for observing the film-forming properties after carbonization.
[0020] In some embodiments, the heating rate to reach the sintering temperature is 2-5° C. / min.
[0021] In the technical solution of the implementation mode of the present application, the sintering temperature is reached at the heating rate, which is beneficial to the full carbonization of the carbon source during the heating stage, thereby improving the accuracy of the evaluation.
[0022] In some embodiments, the sintering time is 0.1 to 5 hours.
[0023] In the technical solution of the implementation mode of the present application, the sintering time is within the above range, the time consumption is short, and the carbon source can be fully carbonized, thereby improving the accuracy of the evaluation.
[0024] In some embodiments, the carbon layer has a thickness of 5 to 10 nm.
[0025] In the technical solution of the implementation mode of the present application, the thickness of the carbon layer is within the above range, which can reflect the actual situation of the carbon source on the surface of the positive electrode active material or the negative electrode active material and improve the accuracy of the evaluation.
[0026] In some embodiments, after the carbon layer is formed, the method further includes observing the density of the carbon layer and / or observing whether there is free residual carbon in the carbon layer.
[0027] The present application preliminarily analyzes the film-forming property of the carbon source by observing the compactness of the carbon layer and whether there is free residual carbon, that is, whether carbonization can form a stable carbon coating layer on the surface of the material to be coated.
[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0030] Figure 1 This is a graph showing the film-forming properties of the substrate spheres described in some embodiments of the present application. DETAILED DESCRIPTION
[0031] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0033] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0034] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0035] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "2-10" means that all real numbers between "2-10" are listed in this document, and "2-10" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0037] In secondary batteries, positive electrode active materials or negative electrode active materials with poor conductivity, such as polyanionic positive electrode materials lithium iron phosphate or lithium iron manganese phosphate, alloyed negative electrode active materials silicon, etc., can meet the conductivity requirements by forming a carbon coating layer on their surface. Therefore, in practical applications, it is necessary to first evaluate whether the carbon source can improve the conductivity of the material to be coated, and then conduct batch experiments.
[0038] In the prior art, in the face of the above problem, the general method is to ball-mill the carbon source and the material to be coated, spray dry after the particle size reaches the standard, then sinter at high temperature, and finally perform a powder resistance test to confirm whether the carbon source is a suitable coating material. If the conditions are met, the next step of the experiment is carried out; if the conditions are not met, the material to be coated is discarded together.
[0039] The above method has complicated processes and consumes the material to be coated during the experiment. In addition, when the material to be coated is coated with the carbon source, in order to promote the secondary crystallization growth of the material to be coated, the carbonization time is usually set to 12 hours or even longer, which is much longer than the time required for the carbonization of the carbon source itself; therefore, it takes a lot of time to judge whether the electronic conductivity of the carbon layer after the carbonization of the carbon source meets the requirements, resulting in a waste of energy consumption.
[0040] Based on this, the present application provides a method for evaluating the conductivity of a carbon source, which can preliminarily determine whether a certain carbon source is suitable for carbon coating of a material to be coated (i.e., a positive electrode active material or a negative electrode active material), and can also preliminarily determine whether the carbon source has good film-forming properties on the surface of the material to be coated; it can also quickly and inexpensively screen out a carbon source suitable for carbon coating of the material to be coated from a large number of carbon sources; the evaluation method is time-saving, highly accurate, reduces waste of materials to be coated, and is low-cost.
[0041] [Evaluation method of carbon source electrical conductivity]
[0042] The present application provides a method for evaluating the conductivity of a carbon source, the method comprising the following steps: setting the conductivity to ≤10 4 S / m (e.g. 10 -18 S / m, 10 -16 S / m, 10 -14 S / m, 10 -12 S / m, 10 -10 S / m, 10 -8 S / m, 10 -6 S / m, 10 -4 S / m, 10 -2 S / m, 10S / m, 10 2 S / m, etc.) and a rough surface substrate ball are placed in a carbon source and / or a solution of a carbon source, the substrate ball is taken out and sintered to form a carbon layer, the resistance value of the carbon layer is tested, and the conductivity of the carbon source is evaluated.
[0043] In the present application, the conductivity of the base ball is measured by the thermal diffusion method, that is, the conductivity is calculated by heating the ceramic surface and measuring the heat conduction rate. Specifically, a pyroelectric device or a laser flash method can be used for heating, and then the temperature difference between two positions can be measured to obtain the resistance of the two positions. There is a one-to-one correspondence between temperature and resistance, and then the conductivity is calculated. The relationship is as follows: conductivity K = 1 / ρ (S / m), resistivity ρ = ΔR × A / L, ΔR is the resistance difference between the two positions, A is the surface area of the sphere, and L is the diameter.
[0044] In the technical solution of the embodiment of the present application, the evaluation method uses a substrate ball with low conductivity and rough surface as the core, places it in a carbon source and / or a solution of a carbon source, takes it out and sinters it to form a carbon layer coated on the surface of the substrate ball, and tests the resistance value. In the evaluation method, there is no need to prepare the material to be coated and the carbon source into a composite material through a complicated process for judgment. It is only necessary to simply and quickly evaluate at the carbon source level whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the material to be coated, and serve as an advance guide. The evaluation method is convenient and fast, can save energy and reduce consumption, and does not waste the material to be coated. When rapid screening is required from multiple carbon sources, the advantages of energy saving and efficiency improvement are obvious.
[0045] In the technical solution of the embodiment of the present application, the form of the carbon source is not limited, and can be liquid or non-liquid (such as gel or solid); when the carbon source is liquid, in the evaluation method, the matrix ball can be directly placed in the carbon source, or the carbon source can be first mixed with a solvent to form a solution of the carbon source, and then the matrix ball is placed in the carbon source; when the carbon source is in a gel state, if the carbon source has poor fluidity, the carbon source needs to be dissolved in a solvent to form a solution of the carbon source, and then the matrix ball is placed in the carbon source; when the carbon source is solid, the carbon source is first dissolved in a solvent to form a solution of the carbon source, and then the matrix ball is placed in the carbon source.
[0046] In some embodiments, the present application does not limit the type of carbon source, and according to the type of positive electrode active material or negative electrode active material, the carbon source to be screened is selected, and then the conductivity is evaluated using the method described in the present application. For example, glucose, dextran, starch, sucrose, dextrin, cellulose, carboxymethyl cellulose, cyclodextrin, amino acid, citric acid, polyvinyl alcohol, polyethylene glycol, polyethylene, polystyrene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyarylate, polyacrylonitrile, polyvinylidene fluoride, polyvinyl pyrrolidone, sodium polyacrylate, polyacrylamide, aniline, melamine, dopamine, acetonitrile, aqueous polyimide, tannic acid, ascorbic acid, etc.
[0047] In some embodiments, when the carbon source is non-liquid, it can be a water-soluble carbon source, an alcohol-soluble carbon source, or a carbon source soluble in other solvents. The present application does not limit the solubility of the carbon source, nor does it limit the type of solvent. A suitable solvent is selected according to the adaptability of the type of the carbon source. For example, polyvinylidene fluoride is dissolved in nitrogen methyl pyrrolidone, polyacrylonitrile and polystyrene are dissolved in dimethylformamide, polyethylene, polyethylene terephthalate, and polybutylene terephthalate are dissolved in chloroform, polypropylene is dissolved in toluene, and melamine is dissolved in methanol.
[0048] In some embodiments, the carbon source solution also includes an auxiliary agent. The present application does not limit the type of the auxiliary agent, and the auxiliary agent can be selected as needed. For example, some co-solvents can be selected.
[0049] In the present application, the base ball can be purchased commercially or made at home.
[0050] Specifically, the surface roughness of the base ball is: grinding, polishing, electroplating, chemical treatment and other surface treatment methods are used to remove burrs and residues left by processing, change the surface finish and morphology, and control the roughness.
[0051] The diameter of the base ball: Based on the precision ball processing of the spiral motion mode, the rotational motion of the spiral grinding groove continuously changes the rotation axis angle of the ball blank during the grinding process, realizes full envelope processing, and controls the diameter of the base ball.
[0052] In some embodiments, the conductivity of the substrate sphere is 10 -8 ~10 4 S / m, e.g. 10 -6 S / m, 10 -4 S / m, 10 - 2 S / m, 10S / m, 10 2 S / m, etc.
[0053] In the technical solution of the embodiment of the present application, the conductivity of the base ball is within the range, belonging to a semiconductor material, and can effectively evaluate whether the carbon coating layer of the carbon source after carbonization can effectively improve the electronic conductivity of the semiconductor material to be coated.
[0054] In some embodiments, the material of the base ball includes silicon carbide.
[0055] In the technical solution of the embodiment of the present application, the material of the base ball is within the above-mentioned range, the raw material source is wide, the cost is low, the hardness is high, and it is resistant to high temperature, which can meet the requirements of sintering with a variety of carbon sources. It can also evaluate at low cost and efficiently whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the semiconductor material to be coated.
[0056] In some embodiments, the conductivity of the substrate ball is less than 10 -14 S / m, e.g. 10 -16 S / m, 10 -18 S / m, 10 -20 S / m, etc.
[0057] In the technical solution of the embodiment of the present application, the conductivity of the base ball is within the range, belonging to an insulating material, and can effectively evaluate whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the insulating material to be coated.
[0058] In some embodiments, the material of the base ball includes any one of aluminum oxide, zirconium dioxide, or silicon dioxide, or a combination of at least two of them.
[0059] In the technical solution of the embodiment of the present application, the material of the base ball is within the above-mentioned range, the raw material source is wide, the cost is low, and the insulation is good. It can low-cost and efficient evaluate whether the carbon coating layer after carbonization of the carbon source can effectively improve the electronic conductivity of the insulating material to be coated.
[0060] In some embodiments, the surface roughness of the base ball is 0.4 to 6.0 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, etc.
[0061] In the present application, the surface roughness of the substrate ball is measured by a stylus method, that is, a diamond stylus with a tip curvature radius of about 2 microns is slowly slid along the measured surface, and the up and down displacement of the diamond stylus is converted into an electrical signal by an electrical length sensor, which is amplified, filtered, and calculated, and the surface roughness value is indicated by a display instrument.
[0062] In the technical solution of the embodiment of the present application, the surface roughness of the substrate ball is within the above range, the carbon source or the solution of the carbon source has good wettability on its surface, the substrate ball can have a good interaction force with the carbon source, which is conducive to forming a carbon layer that meets the requirements.
[0063] In some embodiments, the diameter of the base ball is 0.8-1.5 cm, such as 1 cm, 1.2 cm, 1.4 cm, etc.
[0064] In the technical solution of the embodiment of the present application, the diameter of the substrate ball is within the above range, and the tension of the carbon source on its surface is moderate, which is conducive to the experiment and convenient for observing the film-forming properties after carbonization.
[0065] In some embodiments, the heating rate to reach the sintering temperature is 2-5°C / min, for example, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, etc.
[0066] In the technical solution of the embodiment of the present application, the sintering temperature is reached at the heating rate, which is beneficial to the full carbonization of the carbon source during the heating stage, thereby improving the accuracy of the evaluation.
[0067] In some embodiments, the sintering time is 0.1 to 5 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, etc.
[0068] In the technical solution of the embodiment of the present application, the sintering time is within the above range, which is short and the carbon source can be fully carbonized, thereby improving the accuracy of the evaluation.
[0069] In some embodiments, the thickness of the carbon layer is 5-10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm, etc.
[0070] In the technical solution of the embodiment of the present application, the thickness of the carbon layer is within the above range, which can reflect the actual situation of the carbon source on the surface of the positive electrode active material or the negative electrode active material and improve the accuracy of the evaluation.
[0071] The above evaluation method of the present application is applicable to the screening of carbon coating materials of positive electrode active materials or negative electrode active materials with poor conductivity in any secondary battery, that is, the screening of carbon sources.
[0072] In some embodiments, after the carbon layer is formed, the method further includes observing the density of the carbon layer and / or observing whether there is free residual carbon in the carbon layer.
[0073] In the technical solution of the embodiment of the present application, by observing the density of the carbon layer and whether there is free residual carbon, the film-forming property of the carbon source is preliminarily analyzed, that is, whether carbonization can form a stable carbon coating layer on the surface of the material to be coated.
[0074] The following is an illustrative description of the components of a secondary battery.
[0075] Positive electrode
[0076] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector.
[0077] In some embodiments, the positive electrode current collector includes any one or a combination of at least two of a metal foil, a conductive polymer material, a carbon material or a composite current collector. For example, as a metal foil, pure metal, alloy, surface-treated metal, including but not limited to stainless steel, copper, aluminum, nickel, nickel, titanium or silver, etc. can be used. The composite current collector may include a polymer material base and a metal layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.). The present application has no particular restrictions on the type of positive electrode current collector, and any known material can be selected.
[0078] In some embodiments, the positive electrode film layer includes a positive electrode active material and a conductive agent, and optionally, also includes a binder and any other additives (such as a surfactant, etc.).
[0079] In some embodiments, the positive electrode active material may be selected from lithium composite metal oxides containing one or more of the group consisting of cobalt, manganese, and nickel, or lithium-containing olivine-type phosphates containing one or more of iron, cobalt, nickel, and manganese. These positive electrode active materials may be used alone or in combination of two or more. The present application does not particularly limit the type of the positive electrode active material, and any known material may be selected.
[0080] In some embodiments, the lithium composite metal oxide may be selected from LiCoO2, LiMn2O4, LiNiO2, LiCo 1-x Ni x O2(0.01 < x < 1), LiNi x Mn y Co z O2(x + y + z = 1), a solid solution of Li2MnO3 and LiMO2 (M is a transition metal such as Co, Ni, Mn, Fe, etc.), LiNi 1 / 2 Mn 3 / 2 O4, LiFePO4, LiMnPO4, and LiMn 1-x Fe x PO4(0.01 < x < 1), and at least one of them.
[0081] In some embodiments, the lithium-containing olivine-type phosphate includes at least one of lithium iron phosphate (such as LiFePO4 (which may also be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.
[0082] In some embodiments, a part of the lithium composite metal oxide or the lithium-containing olivine-type phosphate may be substituted with other elements, or a part of cobalt, nickel, manganese, and iron may be substituted with one or more elements selected from Co, Mn, Ni, Mg, Al, B, Ti, V, Nb, Cu, Zn, Mo, Ca, Sr, W, and Zr, or coated with a compound containing these other elements or a carbon material.
[0083] In some embodiments, the conductive agent includes any one or a combination of at least two of carbon black (such as acetylene black, Ketjen black, Super P, etc.), graphite, superconducting carbon, carbon dots, carbon nanotubes, graphene, or carbon nanofibers. The present application does not particularly limit the type of the conductive agent, and any known material may be selected.
[0084] In some embodiments, the binder includes any one of polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber or polyacrylic acid, or a combination of at least two thereof. The present application has no particular limitation on the type of binder, and any known material may be selected. The present application has no particular limitation on the type of binder, and any known material may be selected.
[0085] In some embodiments, the method for preparing the positive electrode sheet comprises the following steps:
[0086] The positive electrode active material and the conductive agent are dissolved in a solvent (such as dimethylformamide, etc.), and optionally, a binder and any other components are also included to form a positive electrode slurry, which is coated on a positive electrode collector, and then dried, cold pressed, and cut to obtain the positive electrode sheet.
[0087] Negative electrode
[0088] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector.
[0089] In some embodiments, the negative electrode current collector may be a metal foil, a conductive polymer material, a carbon material or a composite current collector. For example, as the metal foil, pure metal, alloy, surface-treated metal, including but not limited to stainless steel, copper, aluminum, nickel, nickel, titanium or silver, etc. may be used. The composite current collector may include a polymer material base and a metal layer. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.). The present application has no particular restrictions on the type of negative electrode current collector, and any known material may be selected.
[0090] In some embodiments, the negative electrode film layer includes a negative electrode active material and a conductive agent, and optionally, also includes a binder and any other additives (such as a thickener, etc.).
[0091] In some embodiments, the negative electrode active material includes any one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, or lithium titanate, or a combination of at least two thereof. The present application has no particular limitation on the type of negative electrode active material, and any known material may be selected.
[0092] In some embodiments, the binder includes any one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose or polyethylene oxide, or a combination of at least two thereof. The present application has no particular limitation on the type of binder, and any known material can be selected.
[0093] In some embodiments, the conductive agent includes any one or a combination of at least two of carbon black (such as acetylene black, Ketjen black, Super P, etc.), graphite, superconducting carbon, carbon dots, carbon nanotubes, graphene or carbon nanofibers. The present application has no particular restrictions on the type of conductive agent, and any known material can be selected.
[0094] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps:
[0095] The negative electrode active material and the conductive agent are dissolved in a solvent (such as water, etc.), and optionally, a binder and any other components are also included to form a negative electrode slurry, which is coated on a negative electrode collector, and then dried, cold pressed, and cut to obtain the negative electrode sheet.
[0096] Electrolytes
[0097] The electrolyte plays a role in conducting ions between the cathode electrode and the anode electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0098] The liquid electrolyte includes an electrolyte salt and a solvent.
[0099] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0100] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone. The solvent can also be selected from ether solvents. Ether solvents can include at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran or diphenyl ether and crown ether.
[0101] In some embodiments, the gel electrolyte includes a polymer as a skeleton network and can be used in combination with an ionic liquid-lithium salt.
[0102] In some embodiments, the solid electrolyte includes a polymer solid electrolyte, an inorganic solid electrolyte, and a composite solid electrolyte.
[0103] In some embodiments, the polymer of the polymer solid electrolyte may include at least one of polyether (polyethylene oxide), polysiloxane, polycarbonate, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, a single ion polymer, a polyionic liquid, or cellulose.
[0104] In some embodiments, the inorganic solid electrolyte can be an oxide solid electrolyte (crystalline perovskite, sodium superconducting ion conductor, garnet, amorphous LiPON film), a sulfide solid electrolyte (crystalline lithium superion conductor (lithium germanium phosphosulfide, silver germanium sulfide), amorphous sulfide) and at least one of a halide solid electrolyte, a nitride solid electrolyte or a hydride solid electrolyte.
[0105] In some embodiments, the composite solid electrolyte is formed by adding an inorganic solid electrolyte filler to a polymer solid electrolyte.
[0106] Isolation film
[0107] The present application has no particular limitation on the type of separator, and any known porous structure separator for secondary batteries can be selected.
[0108] In some embodiments, the isolation membrane includes one or more of a glass fiber separator, a non-woven fabric film, a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, and a multilayer composite film of one or more of them.
[0109] Secondary battery preparation method
[0110] In some embodiments, the secondary battery can be prepared by the following method: stack and wind the above-mentioned positive electrode plate, isolation film, and negative electrode plate in order to obtain a battery cell; place the battery cell in an outer package, add electrolyte, and obtain a secondary battery after packaging, standing, formation, aging and other processes.
[0111] [Batteries, battery modules, battery packs]
[0112] In some embodiments, battery cells may be assembled into batteries; batteries may be assembled into battery modules, and the number of batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0113] In some embodiments, the batteries can also be assembled into battery packs.
[0114] In some embodiments, the battery modules may also be assembled into a battery pack. The number of battery modules contained in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0115] [Electrical devices]
[0116] The present application provides an electrical device, which includes the battery cell or battery.
[0117] In some embodiments, the electrical device includes at least one of the battery modules or battery packs provided in any embodiment of the present application.
[0118] The secondary battery, battery module or battery pack described in the present application can be used as a power source of the electrical device, or as an energy storage unit of the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0119] [Example]
[0120] Example 1
[0121] Evaluation of electronic conductivity and film-forming properties of liquid carbon sources
[0122] (1) Take 20 g of liquid carbon source (water-based polyimide) in a beaker and place a base ball (made of zirconium dioxide with a conductivity of 10 -15 S / m, surface roughness of 4 μm, diameter of 1.2 cm) and then taken out with tweezers and placed in a graphite crucible;
[0123] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750° C. at a heating rate of 5° C. / min, and sintering for 2 hours. After the temperature of the high-temperature sintering furnace is lowered to room temperature, taking out the substrate ball coated with a 9 nm carbon layer;
[0124] (3) Using a multimeter to measure the electronic conductivity of the carbon layer on the surface of the substrate ball, and at the same time observing the film-forming property of the liquid carbon source after carbonization and whether there is residual carbon;
[0125] Among them, the method for testing electronic conductivity is to use a multimeter to adjust the ohm range at room temperature, clamp the ball at the two farthest points, that is, the distance is the diameter of the ball, and observe the multimeter display number.
[0126] Example 2
[0127] Evaluation of the electronic conductivity and film-forming properties of water-soluble solid carbon sources
[0128] (1) Place 50 mL of pure water in a beaker, take 20 g of solid carbon source (glucose) in the beaker, stir with a glass rod to fully dissolve the carbon source, and place the base ball (made of zirconium dioxide, with a conductivity of 10 -15 S / m, surface roughness of 4 μm, diameter of 1.2 cm) and then taken out with tweezers and placed in a graphite crucible;
[0129] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750° C. at a heating rate of 5° C. / min, and sintering for 2 hours. After the temperature of the high-temperature sintering furnace is lowered to room temperature, taking out the substrate ball coated with an 8 nm carbon layer;
[0130] (3) Measure the electronic conductivity of the carbon layer on the surface of the substrate ball (the specific test method is the same as that in Example 1), and observe the film-forming property of the liquid carbon source after carbonization and whether there is residual carbon.
[0131] Example 3
[0132] Evaluation of the electronic conductivity and film-forming properties of alcohol-soluble solid carbon sources
[0133] (1) Place 50 mL of anhydrous ethanol in a beaker, take 20 g of solid carbon source tris (phenolic resin) in the beaker, stir with a glass rod to fully dissolve the carbon source, and place the base ball (made of zirconium dioxide, with a conductivity of 10 -15 S / m, surface roughness of 4 μm, diameter of 1.2 cm) and then taken out with tweezers and placed in a graphite crucible;
[0134] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750° C. at a heating rate of 5° C. / min, and sintering for 2 hours. After the temperature of the high-temperature sintering furnace is reduced to room temperature, taking out the substrate ball coated with a 10 nm carbon layer;
[0135] (3) Measure the electronic conductivity of the carbon layer on the surface of the substrate ball (the specific test method is the same as that in Example 1), and observe the film-forming property of the liquid carbon source after carbonization and whether there is residual carbon.
[0136] Embodiment 4-5
[0137] The difference between Example 4-5 and Example 1 is that the liquid carbon source 1 is replaced by liquid carbon source 2 (polytetrafluoroethylene concentrated dispersion, Example 4) and liquid carbon source 3 (polysiloxane, Example 5), and the rest is the same as Example 1.
[0138] Embodiment 6-9
[0139] The difference between Examples 6-9 and Example 1 is that the surface roughness of the base ball is different, which are 0.2 μm (Example 6), 0.4 μm (Example 7), 6 μm (Example 8) and 6.2 μm (Example 9), respectively. The rest are the same as Example 1.
[0140] Examples 10-13
[0141] The difference between Examples 10-13 and Example 1 is that the diameters of the base balls are different, which are 0.6 cm (Example 10), 0.8 cm (Example 11), 1.5 cm (Example 8) and 1.7 μm (Example 13), respectively. The rest are the same as Example 1.
[0142] Embodiment 14
[0143] (1) Take 20 g of liquid carbon source tetrakis (water-based styrene-butadiene rubber) in a beaker and place a base ball (made of a material with an electrical conductivity of 10 - 15 S / m of alumina and conductivity is 10 -15 A mixture of 200 μm and 100 μm of silicon dioxide (with a mass ratio of 1:1, a surface roughness of 2 μm, and a diameter of 1 cm) was immersed in the mixture, and then the mixture was taken out with tweezers and placed in a graphite crucible;
[0144] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750° C. at a heating rate of 2° C. / min, and sintering for 0.5 h. After the temperature of the high-temperature sintering furnace is reduced to room temperature, taking out the substrate ball coated with a 5 nm carbon layer;
[0145] (3) Measure the electronic conductivity of the carbon layer on the surface of the substrate ball (the specific test method is the same as that in Example 1), and observe the film-forming property of the liquid carbon source after carbonization and whether there is residual carbon.
[0146] Embodiment 15
[0147] (1) Take 20g of liquid carbon source 5 (ZY-9408 leveling agent, the basic composition is a hydrocarbon-oxygen cyclic compound) in a beaker and place the base ball (material is a conductivity of 10 -8 S / m of silicon carbide and a conductivity of 10 4 A mixture of S / m silicon carbide, with a mass ratio of 1:1, a surface roughness of 3.2 μm, and a diameter of 1.2 cm) was immersed, and then taken out with tweezers and placed in a graphite crucible;
[0148] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750° C. at a heating rate of 5° C. / min, and sintering for 5 hours. After the temperature of the high-temperature sintering furnace is reduced to room temperature, taking out the substrate ball coated with a 10 nm carbon layer;
[0149] (3) Measure the electronic conductivity of the carbon layer on the surface of the substrate ball (the specific test method is the same as that in Example 1), and observe the film-forming property of the liquid carbon source after carbonization and whether there is residual carbon.
[0150] Comparative Example 1
[0151] (1) 20 g of the liquid carbon source 1 described in Example 1 and 100 g of the positive electrode active material (lithium iron phosphate) were mixed, ball milled for 12 h, spray dried for 2 h, and then placed in a graphite crucible;
[0152] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750°C at a heating rate of 5°C / min, and sintering for 12 hours. After the temperature of the high-temperature sintering furnace is lowered to room temperature, taking out the positive electrode active material coated with a 9 nm carbon layer;
[0153] (3) Measuring the electronic conductivity of the positive electrode active material obtained in step (2), and observing the film-forming property of the liquid carbon source after carbonization and the presence of residual carbon.
[0154] Comparative Example 2
[0155] (1) 50 mL of pure water was placed in a beaker, 20 g of the solid carbon source 2 described in Example 2 was taken into the beaker, and the carbon source was stirred with a glass rod to fully dissolve, and then mixed with 200 g of the positive electrode active material (lithium iron phosphate), ball milled for 12 h, spray dried for 2 h, and then placed in a graphite crucible;
[0156] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750°C at a heating rate of 5°C / min, and sintering for 12 hours. After the temperature of the high-temperature sintering furnace is lowered to room temperature, taking out the positive electrode active material coated with an 8 nm carbon layer;
[0157] (3) Measuring the electronic conductivity of the positive electrode active material obtained in step (2), and observing the film-forming property of the liquid carbon source after carbonization and the presence of residual carbon.
[0158] Comparative Example 3
[0159] (1) Place 50 mL of anhydrous ethanol in a beaker, take 20 g of the solid carbon source 2 described in Example 3 into the beaker, stir with a glass rod to fully dissolve the carbon source, then mix with 200 g of the positive electrode active material (lithium iron phosphate), ball mill for 12 h, spray dry for 2 h, and then place in a graphite crucible;
[0160] (2) transferring the graphite crucible to a high-temperature sintering furnace, heating the temperature to 750°C at a heating rate of 5°C / min, and sintering for 12 hours. After the temperature of the high-temperature sintering furnace is lowered to room temperature, taking out the positive electrode active material coated with a 10 nm carbon layer;
[0161] (3) Measuring the electronic conductivity of the positive electrode active material obtained in step (2), and observing the film-forming property of the liquid carbon source after carbonization and the presence of residual carbon.
[0162] Comparative Examples 4-5
[0163] The difference between Comparative Example 4-5 and Comparative Example 1 is that the liquid carbon source 1 described in Example 1 is replaced by the liquid carbon source 2 described in Example 4 and the liquid carbon source 3 described in Example 5, and the rest is the same as Comparative Example 1.
[0164] Performance Testing
[0165] (1) Electrical conductivity: The surface resistance of the substrate ball coated with the carbon layer formed by the evaluation method is tested using a multimeter;
[0166] The powder resistance of the positive electrode active material coated with a carbon layer was tested using a four-probe method.
[0167] (2) Film-forming property: observe the density of the carbon layer and whether there is free residual carbon. The film-forming property is divided into Grade 1, Grade 2, Grade 3 and Grade 4 from good to bad. Among them, Grade 1 has poor density and a residual carbon rate of ≥20%; Grade 2 has fair density and a residual carbon rate of 10% to 20%, but not equal to 20%; Grade 3 has good density and a residual carbon rate of 5% to 10%, but not equal to 10%; Grade 4 has excellent density and a residual carbon rate of <5%.
[0168] (3) Duration: The duration of the entire evaluation process is calculated based on the evaluation method.
[0169] (4) Accuracy: For the same carbon source, the evaluation method described in the present application (example) and the traditional evaluation method (comparative example) were used to prepare a composite material (a substrate ball coated with a carbon layer and a positive electrode active material coated with a carbon layer). The conductivity result of the example was divided by the result of the corresponding comparative example to determine the accuracy of the evaluation method described in the present application.
[0170] The test results are summarized in Table 1 and Figure 1 middle.
[0171] Table 1
[0172]
[0173] “——” indicates that no test is required or the data has not been tested.
[0174] According to the data in Table 1, the evaluation method described in the present application can preliminarily determine whether a certain carbon source is suitable for carbon-coating the material to be coated, and can also preliminarily determine whether the carbon source has good film-forming properties on the surface of the material to be coated; it can also quickly and inexpensively screen out carbon sources suitable for carbon-coating the material to be coated from a large number of carbon sources; the evaluation method is time-saving, highly accurate, reduces waste of materials to be coated, and is low-cost.
[0175] Analysis of Example 1 and Comparative Example 1 shows that Example 1 takes much less time than Comparative Example 1. Based on the results of Example 1, it is preliminarily judged that the electronic conductivity of the liquid carbon source 1 is at the kΩ level. Figure 1 As shown, the carbon layer formed on the surface of the substrate ball after the liquid carbon source is carbonized has less residual carbon and good film-forming property, which is similar to the result of Comparative Example 1. The preliminary evaluation result is accurate. Example 2-5 and Comparative Example 2-5 have similar results.
[0176] From the analysis of Examples 1-5, it can be seen that the conductivity of the carbon sources is preliminarily judged to be in the order of Example 1, Example 4, Example 3, Example 5 and Example 2 from good to bad; the comparative examples 1-5 are accurately tested, proving that the conductivity of the carbon sources is in the order of comparative example 1, comparative example 4, comparative example 3, comparative example 5 and comparative example 2 from good to bad; the results of the two are consistent, proving that the evaluation method of the present application has high accuracy and is suitable for quickly and low-costly screening out carbon sources suitable for carbon coating of positive electrode active materials or negative electrode active materials from a large number of carbon sources.
[0177] Analysis of Examples 6-9 shows that the evaluation methods of Examples 6 and 9 are not as good as those of Examples 7-8, which proves that the surface roughness of the substrate ball within the range is more conducive to judging the conductivity of the carbon source.
[0178] Analysis of Examples 10-13 shows that the evaluation methods of Examples 10 and 13 are not as good as those of Examples 11-12, which proves that the diameter of the substrate ball within the range is more conducive to judging the conductivity of the carbon source.
[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for evaluating the conductivity of a carbon source, characterized in that: The evaluation method comprises the following steps: setting the conductivity ≤10 4 The substrate ball with S / m and rough surface is placed in a carbon source and / or a solution of a carbon source, the substrate ball is taken out and sintered to form a carbon layer, the resistance value of the carbon layer is tested, and the conductivity of the carbon source is evaluated.
2. The evaluation method according to claim 1, characterized in that: The conductivity of the substrate ball is 10 -8 ~10 4 S / m.
3. The evaluation method according to claim 1 or 2, characterized in that: The material of the base ball includes silicon carbide.
4. The evaluation method according to claim 1, characterized in that: The conductivity of the base ball is less than 10 -14 S / m.
5. The evaluation method according to claim 1 or 4, characterized in that: The material of the base ball includes any one of aluminum oxide, zirconium dioxide or silicon dioxide or a combination of at least two of them.
6. The evaluation method according to any one of claims 1 to 5, characterized in that: The surface roughness of the base ball is 0.4-6.0 μm.
7. The evaluation method according to any one of claims 1 to 6, characterized in that: The diameter of the base ball is 0.8-1.5 cm.
8. The evaluation method according to any one of claims 1 to 7, characterized in that: The heating rate to reach the sintering temperature is 2 to 5°C / min.
9. The evaluation method according to any one of claims 1 to 8, characterized in that: The sintering time is 0.1 to 5 hours.
10. The evaluation method according to any one of claims 1 to 9, characterized in that: The thickness of the carbon layer is 5-10 nm.
11. The evaluation method according to any one of claims 1 to 10, characterized in that: After the carbon layer is formed, the method further includes observing the density of the carbon layer and / or observing whether there is free residual carbon in the carbon layer.
Citation Information
Patent Citations
Carbon coating method for electrode active material of lithium ion battery
CN104282887A
Positive plate, lithium-ion battery positive lithium-supplementing material and preparation method of material
CN109786746A
Preparation method of lithium-doped silicon-oxygen-carbon / graphite composite negative electrode material
CN110165160A
Silicon-based negative electrode material, preparation method thereof and lithium ion battery
CN111342020A
Silicon-based negative electrode material, and preparation method and application thereof
CN112952059A